(untitled) (Scientific journal of the Fergana State University, 2022)
The article discusses the mistakes made by students, and work on them, which is one of the ways to improve the quality of math lessons. In order to systematize and classify mistakes made by students when performing control, independent and homework assignments, the main types of mistakes made by students in mathematics were identified.